Targeting the Oxidative Stress Response System of Fungi with Redox-Potent Chemosensitizing Agents - Kim, Jong H.; Chan, Kathleen L.; Faria, Natalia C.G.; Martins, M. de L.; Campbell, Bruce C. (Frontiers in Microbiology, 2012)
The cellular antioxidation system is a target in the antifungal action of amphotericin B (AMB) and itraconazole (ITZ), in filamentous fungi. The sakAΔ mutant of Aspergillus fumigatus, a mitogen-activated protein kinase (MAPK) gene deletion mutant in the antioxidation system, was found to be more sensitive to AMB or ITZ than other A. fumigatus strains, a wild type and a mpkCΔ mutant (MAPK gene deletion mutant in polyalcohol sugar utilization system). The sakAΔ mutant showed no growth at 0.5 μg mL-1 of ITZ or reduced growth at 1.0 to 2.0 μg mL-1 of AMB, while the other strains exhibited robust growth. Complete fungal kill (≥ 99.9%) by ITZ or AMB was achieved by much lower dosages for the sakAΔ mutant than for the other strains. SakA and MpkC appear to have overlapping roles in marshalling the oxidative stress response under treatment by an organic peroxide, tert-butyl hydroperoxide (t-BuOOH), or hydrogen peroxide (H2O2). The SakA signalling pathway was found to be responsible for fungal tolerance to AMB or ITZ toxicity. It appears msnA, an Aspergillus ortholog to Saccharomyces cerevisiae MSN2 (encoding a stress-responsive C2H2-type zinc-finger regulator) and sakA and/or mpkC (upstream MAPKs) are in the same stress response network under t-BuOOH-, H2O2- or AMB-triggered toxicity. Of note is that ITZ-sensitive yeast pathogens (Candida krusei and Cryptococcus neoformans) were also sensitive to t-BuOOH, showing a connection between ITZ toxicity and oxidative stress response. This was shown by enhanced antifungal activity of AMB or ITZ when co-applied with redox-potent natural compounds, 2,3-dihydroxybenzaldehyde, thymol or salicylaldehyde, as chemosensitizing agents. Hence, redox compounds, which target the antioxidation system in fungi, possess a potent chemosensitizing capacity to enhance efficacy of conventional drugs inducing oxidative stress. Such chemosensitization can reduce costs and alleviate negative side effects associated with current antifungal treatments.